Early Intervention of Preschoolers with Speech and Language Impairments by Parents as First Teachers: A Case Study on Four Families in Kuching, Sarawak - Awang Jamalludin, Fadzillah (Faculty of Cognitive Sciences and Human Development, 2017)
Parental involvement during early childhood development is important especially when the child has learning disabilities. This research aims to study the effectiveness of parental-based speech training programs for preschoolers with Speech Language Impairments (SLI) in a localized setting. The method used was qualitative and data was collected from selected preschoolers (N = 5) with different types of SLI symptoms. Each participant was assessed using a standardized assessment protocol to measure his/her language scale. The participants were given the intervention program by their own parents using the Hanen’s It Takes Two to Talk program. The progress of each subject and observations from these sessions were documented. The participants were assessed again once the intervention had been implemented. Substantial results were achieved when all subjects showed improvements in language comprehension and production skills. These results highlight the importance of parental involvement as first teachers in the early intervention of children with SLI.